Serum Irisin and Asprosin Levels as Potential Biomarkers an Type 2 Diabetes Mellitus and its Renal Complications: A Biochemical Investigation of Hormonal and Metabolic Profiles - Aqeel M. Rasool; Alaa Hussein J. Al-Qaisi (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
This study investigates the levels of asprosin and irisin in patients with type 2 diabetes mellitus (T2DM) and diabetic nephropathy (DN), and evaluates their relationships with insulin resistance, glycemic control, and renal function. Additionally, it explores their diagnostic performance as potential non-invasive biomarkers for the early detection of DN using ROC curve analysis. A controlled prospective study was conducted involving 130 participants, categorized into healthy controls, T2DM patients, and T2DM with DN. Serum asprosin, irisin, and insulin levels were measured using ELISA, while biochemical and renal parameters such as fasting blood glucose, HbA1c, creatinine, urea, and eGFR were assessed using standard spectrophotometric techniques. ROC analysis was employed to assess the diagnostic accuracy of asprosin and irisin. Asprosin levels were significantly elevated, while irisin levels were markedly reduced in DN patients compared to T2DM and control groups (p < 0.001). Moreover, DN patients exhibited higher levels of fasting glucose, HbA1c, HOMA-IR, creatinine, and urea, with lower eGFR, indicating substantial renal dysfunction. ROC analysis revealed that asprosin had an AUC of 0.910 (95% CI: 0.839–0.981), with 90.0% sensitivity and 88.9% specificity at a cutoff value of 11.27 ng/mL. Irisin showed an AUC of 0.886 (95% CI: 0.812–0.960), with 95.0% sensitivity and 71.1% specificity at a 158.25 ng/mL cutoff. Asprosin and irisin are strongly associated with insulin resistance and renal impairment in patients with T2DM and DN. Their high diagnostic performance supports their utility as promising non-invasive biomarkers for the early detection and monitoring of diabetic nephropathy progression.